Predictors of psychological distress in low‐income mothers over the first postpartum year. Issue 3 (19th March 2019) - Adynski, Harry; Zimmer, Catherine; Thorp, John; Santos, Hudson P
Abstract: Up to 25% of postpartum women experience psychological distress including stress, depressive, or anxiety symptoms during the postpartum period. The purpose of this study was to explore the extent to which social determinants of health and allostatic load score, a 10‐item index of biologic measures of chronic stress, predict psychological distress in low‐income pregnant women over the first postpartum year. We conducted a secondary data analysis of the Child Community Health Research Network data set. The psychological distress outcome variables were perceived stress ( n = 842), depression ( n = 845), and anxiety ( n = 846) symptoms, all measured categorically over the first year postpartum (T1:1 month, T2: 24–29 weeks, and T3: 50–65 weeks). Our predictors were social determinants of health (e.g., demographics, maternal hardship, percent poverty level, interpersonal violence, and food security) and allostatic load score. Generalized linear mixed models were used to determine which predictors were significantly associated with psychological distress symptoms across the first postpartum year. Interpersonal violence was a statistically significant risk factor for stress, depression, and anxiety symptoms over the first year postpartum. Other significant risk factors included low‐income level, nativity, and perceived food security. Receiving food stamps was a significant protective factor for stress symptoms. The significance of risk factors for psychological distress, both modifiable and nonmodifiable, can be used as potential targets for further research, screening, and intervention. Future work should explore why and in what conditions these risk factors vary over time.